When the King turns Jester: A Carnivalesque Analysis of Police Outreach on Social Media in Kerala - Charles, Drupa Dinnie; Pal, Joyojeet (The 11th International Development Informatics Association conference (IDIA2020), 2020)
As bureaucratic organizations enter social media spaces for public outreach, the organization of their communication assumes forms more suited to the needs, requirements and tastes of a digital society. Successfully interacting with new media users requires that the organization shed bureaucratic formality and appropriate a social media personality, with its language and viral digital artefacts. The study examines the digital approach of the Kerala Police in its use of memes based on popular Malayalam cinema, a sub-literacy that the bureaucracy shares with the public. Using a mix of interpretive examination of memes and interviews with the police, we use a carnivalesque frame to highlight ways in which the Kerala Police subverts the negative discourses related to police identity and police-public interaction through comic memes. We propose that the choice of a means of outreach that has a greater affective impact on the middle-classes, rather than the poor, offers insight into a specific moment in state-citizen relations where a bureaucratic organization’s use of technology becomes the means of defining its approachability. This case also highlights the prerogative institutions have in creating solid online presences to deal with new forms of informational attacks that are enabled by viral social media.